Positioning a Novel Transcutaneous Bone Conduction Hearing Implant: a Systematic Anatomical and Radiological Study to Standardize the Retrosigmoid Approach, Correlating Navigation-guided, and Landmark-based Surgery. Issue 4 (April 2018) - Arnold, Heinz; Schulze, Maximilian; Wolpert, Stephan; Hirt, Bernhard; Tropitzsch, Anke; Zimmermann, Rainer; Radeloff, Andreas; Löwenheim, Hubert; Reimann, Katrin
Abstract : Hypothesis: Anatomical and radiological evaluation improves safety and accuracy of the retrosigmoid approach for positioning a transcutaneous bone conduction implant and provides anatomical reference data for standardized, landmark-based implantation at this alternative site. Background: The primary implantation site for the floating mass transducer of a novel bone conduction hearing implant is the mastoid. However, anatomical limitations or previous mastoid surgery may prevent mastoid implantation. Therefore, the retrosigmoid approach has been introduced as an alternative. Methods: Mastoid and retrosigmoid implantation sites were radiologically identified and evaluated in preoperative computed tomography scans of anatomical head specimens. Navigation-guided implantation was then performed in the retrosigmoid site (n = 20). The optimal retrosigmoid position was determined in relation to both the asterion and the mastoid notch as surgical landmarks in an anatomical coordinate system. Results: Preoperative radiological analysis revealed spatial limitations in the mastoid in 45% of the specimens. Navigation-guided retrosigmoid implantation was possible without affecting the sigmoid sinus in all the specimens. The optimal implantation site was located 1.9 ± 0.1 cm posterior/1.7 ± 0.1 cm inferior to the asterion and 3.3 ± 0.2 cm posterior/2.1 ± 0.1 cm superior to the mastoid notch. Retrosigmoid skull thickness was 6.6 ± 0.4 mm, measured anatomically, 7.0 ± 0.4 mm, measured radiologically and 6.7 ± 0.5 mm, measured with the navigation software. Conclusion: The navigation-guided retrosigmoid approach seemed to be a reliable procedure in all the specimens. Measurements of bone thickness revealed the need for spacers in 95% of the specimens. Reference coordinates of the optimal implantation site are provided and can confirm image-guided surgery or facilitate orientation if a navigation system is not available.